Gifts from the garbage truck : a true story about the things we (don't) throw away - Larsen, Andrew, 1960- (Sourcebooks eXplore, 2024)
What if everywhere you looked, you saw something to make? Instead of seeing something broken, you saw something to fix? Instead of seeing something to throw out, you saw something to give away? This is how Nelson Molina sees the world. A former employee for the New York City sanitation department, Nelson saved over 45,000 objects from the garbage to fix and show his community through his museum, Treasures in the Trash. Explore the hidden potential in what we often discard and think differently about consumption, waste, and the impact of small actions. With themes of upcycling, anti-consumerism, love for community, and finding joy, Gifts from the Garbage Truck inspires kids to think creatively and curiously about what they do (and don't) throw away!